Loss of ancient diversity of xenarthrans and the value of protecting extant armadillos, sloths and anteaters - Vizcaíno, Sergio Fabián (2014)
Armadillos, sloths and anteaters represent a small fragment of a much more diverse fossil assemblage of xenarthrans that includes bizarre forms such as the armored glyptodonts and the giant ground sloths. We reconstruct extinct xenarthrans as living animals, describing their basic biology, behaviors and ecological roles. In this contribution we provide two examples of the ecological diversity of xenarthrans in the geological past that largely surpass the one we know today. One is the Santacrucian fauna that developed in southern Patagonia during the Middle Miocene Climatic Optimum (17 to 15 Ma). The richness of Santacrucian xenarthrans recorded in a single locality comprises 21 genera in seven families, exceeding the present total diversity in the continent as a whole (14 genera within five families). The other is the Lujanian fauna that inhabited the Pampean Region during the late Quaternary (0.130 to 0.07 Ma). The total large mammal (above 100 kg) and megamammal (above a ton) richness during Lujanian times may have been as high as 83 species distributed in 48 genera. Most megaherbivores were xenarthrans, which constituted about 80% of the mammals above 500 kg: at least four genera of glyptodonts (Glyptodontidae) and five genera of ground sloths (Mylodontidae and Megatheriidae). There was also a giant armadillo-like herbivore that must have reached 200 kg (Pampatheriidae). This ancient diversity is lost forever, and we therefore urge that autochthony and past taxonomic richness and ecologic diversity be recognized as values for establishing conservation priorities and policies